Silicon-based negative electrode material and preparation method and application thereof
By using a soft carbon substrate in the silicon negative electrode material to coat nanosilicon and combine conductive carbon materials and fast ion conductors to form negative ion phases, the volume expansion and battery performance problems of silicon negative electrode materials are solved, and the electrochemical performance of lithium-ion batteries is improved and cycle life ensure battery safety.
Patent Information
- Application Number
- CN202411184825.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-27
- Publication Date
- 2025-01-07
AI Technical Summary
The silicon negative electrode material has low first-term efficiency and poor circulation performance caused by the volume expansion effect during lithium embedding and deliquification, and the carbon layer coating destroys the transmission rate balance of electrons and ions, reducing battery performance and safety.
A composite structure of nano-silicon is coated with soft carbon substrate, combined with conductive carbon materials and fast ion conductors, forming a negative ion phase with specific ion conductivity and ionic conductivity activation energy, and is stable in the balanced ion transmission rate through multi-stage calcination treatment. In the carbon layer, mechanical properties are enhanced.
It improves the electrochemical performance and cycle life of lithium-ion batteries, reduces side reactions, increases the volume specific capacity, and ensures the safety of battery use.
Smart Images

Figure CN119275256A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of lithium ion battery energy storage, and in particular to a silicon-based negative electrode material and a preparation method and application thereof. Background Art
[0002] Due to the high capacity of silicon negative electrode, it has been widely studied in the battery field. However, it has a serious volume expansion effect. The huge change of the phase during the lithium insertion and removal process brings it a lower initial efficiency and poor cycle performance, which limits its further development. Combining silicon with carbon is one of the main research directions to solve the volume expansion problem of silicon materials, but the coating of the carbon layer destroys the balance of the transmission rate of electrons and ions, thereby reducing battery performance, shortening the cycle life and increasing battery safety issues. Summary of the invention
[0003] Based on this, it is necessary to provide a silicon-based negative electrode material and its preparation method and application to address the above problems; the silicon-based negative electrode material described in the present invention has both electron-ion conductivity and can be used in lithium-ion batteries to improve battery performance and increase cycle life, which is beneficial to ensuring the safety of battery use.
[0004] A silicon-based negative electrode material comprises a soft carbon substrate and nano-silicon, a conductive carbon material and a fast ion conductor distributed in the soft carbon substrate, wherein the ion conductivity of the fast ion conductor is 10 -5 S cm -1 -10 -2 S cm -1 , the ion conduction activation energy is 0.2eV-0.4eV, and the fast ion conductor forms a negative ion phase on the surface of the conductive carbon material;
[0005] At 200mA·g -1 Under the condition of a current density of , before and after 50 cycles of treatment, the change rate of metal ion concentration on the surface of the silicon-based negative electrode material is less than or equal to 10%.
[0006] In one of the embodiments, after 50 cycles of treatment, the metal ion concentration on the surface of the silicon-based negative electrode material is 750ppm-950ppm.
[0007] In one embodiment, the particle size of the silicon-based negative electrode material is 5 μm-50 μm.
[0008] In one embodiment, in the silicon-based negative electrode material, the mass fraction of the soft carbon substrate is 20%-90%, the mass fraction of the nano-silicon is 5%-70%, the mass fraction of the conductive carbon material is 1%-10%, and the mass fraction of the fast ion conductor is 1%-10%.
[0009] In one embodiment, the conductive carbon material includes at least one of carbon fiber, carbon nanotube, graphene, silicon carbide or carbon felt.
[0010] In one embodiment, the fast ion conductor includes at least one of silver iodide, copper iodide, lithium borate, zirconium oxide, β-alumina or silver sulfide.
[0011] A method for preparing the silicon-based negative electrode material as described above comprises the following steps:
[0012] A soft carbon precursor, nano-silicon, a conductive carbon material and a fast ion conductor are mixed in a solvent to obtain a material, wherein the ionic conductivity of the fast ion conductor is 10 -5 S cm -1 -10 -2 S cm -1 , the ion conductance activation energy is 0.2eV-0.4eV;
[0013] The material is subjected to secondary calcination treatment under protective atmosphere conditions to obtain a silicon-based negative electrode material.
[0014] In one embodiment, based on 100 parts by weight of nano-silicon, the soft carbon precursor is 160 parts by weight to 1600 parts by weight, the conductive carbon material is 10 parts by weight to 100 parts by weight, and the fast ion conductor is 10 parts by weight to 100 parts by weight;
[0015] And / or, the soft carbon precursor includes at least one of asphalt, residual oil, glucose, sucrose, polyvinylidene fluoride, polytetrafluoroethylene or polyimide;
[0016] And / or, the solvent includes at least one of tetrahydrofuran, xylene, n-hexane, ether or ethanol.
[0017] In one embodiment, the secondary calcination treatment includes: pre-calcining at 450°C-700°C for 30min-300min, then heating to 700°C-1000°C at a heating rate of 1°C / min-10°C / min and keeping the temperature for 30min-300min.
[0018] A silicon-based negative electrode material as described above is used in a lithium-ion battery.
[0019] The silicon-based negative electrode material described in the present invention has a composite structure of a soft carbon substrate coated with nano-silicon, and a conductive carbon material and a fast ion conductor are evenly distributed in the soft carbon substrate. On the one hand, a fast ion conductor with specific ionic conductivity and ionic conductivity activation energy is used to form a special negative ion phase near the conductive carbon material, which is beneficial to evenly accelerate the ion transmission rate of the silicon-based negative electrode material and improve the electrochemical performance of the material. After 50 cycles, the metal ion concentration on the surface of the silicon-based negative electrode material changes little, indicating that it is stably present in the carbon layer structure, which is beneficial to improving the electrical performance. On the other hand, the conductive carbon material, as a reinforcing phase of the composite structure, can improve the mechanical properties of the entire composite structure, thereby effectively alleviating the stress caused by the volume expansion of nano-silicon during the charging and discharging process, and greatly improving the cycle life of the battery.
[0020] In addition, after being coated with a soft carbon substrate, the size of nano-silicon is increased to the micron level, which can not only effectively increase the tap density and have a higher volumetric capacity at the same mass loading, but the micron-level specific surface area is also beneficial to reduce side reactions, thereby further improving the electrochemical performance of the battery. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments recorded in the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0022] Figure 1 The voltage-specific capacity charge-discharge curve of a lithium-ion battery assembled with the silicon-based negative electrode material prepared in Example 4 of the present invention measured at 30° C.;
[0023] Figure 2 The voltage-specific capacity charge-discharge curve of a lithium-ion battery assembled with the silicon-based negative electrode material prepared in Comparative Example 3 of the present invention measured at 30° C.;
[0024] Figure 3 The specific charge capacity and coulombic efficiency of a lithium-ion battery assembled with the silicon-based negative electrode material prepared in Example 4 of the present invention after ten cycles at 30° C.;
[0025] Figure 4 The charging specific capacity and coulombic efficiency of a lithium-ion battery assembled with the silicon-based negative electrode material prepared in Comparative Example 3 of the present invention after ten cycles at 30°C. DETAILED DESCRIPTION
[0026] For ease of understanding of the present invention, the present invention will be described in more detail below. However, it should be understood that the present invention can be implemented in many different forms and is not limited to the embodiments or examples described herein. On the contrary, the purpose of providing these embodiments or examples is to make the understanding of the disclosure of the present invention more thorough and comprehensive.
[0027] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those generally understood by those skilled in the art of the present invention. The terms used herein in the specification of the present invention are only for the purpose of describing specific implementation methods or embodiments, and are not intended to limit the present invention. The optional scope of the term "and / or" used herein includes any one of two or more related listed items, and also includes any and all combinations of related listed items, and the combinations include any two related listed items, any more related listed items, or all related listed items.
[0028] The present invention provides a silicon-based negative electrode material, comprising a soft carbon substrate and nano-silicon, a conductive carbon material and a fast ion conductor distributed in the soft carbon substrate, wherein the ion conductivity of the fast ion conductor is 10 -5 S cm -1 -10 -2 S cm -1 , the ion conduction activation energy is 0.2eV-0.4eV, the fast ion conductor forms a negative ion phase on the surface of the conductive carbon material; at 200mA·g -1 At a current density of , before and after 50 cycles of treatment, the change rate of metal ion concentration on the surface of the silicon-based negative electrode material is less than or equal to 10%.
[0029] The silicon-based negative electrode material described in the present invention has a composite structure of a soft carbon substrate coated with nano-silicon, and a conductive carbon material and a fast ion conductor are evenly distributed in the soft carbon substrate. On the one hand, a fast ion conductor with specific ionic conductivity and ionic conductivity activation energy is used to form a special negative ion phase near the conductive carbon material, which is beneficial to evenly accelerate the ion transmission rate of the silicon-based negative electrode material and improve the electrochemical performance of the material. After 50 cycles, the metal ion concentration on the surface of the silicon-based negative electrode material changes little, indicating that it is stably present in the carbon layer structure, which is beneficial to improving the electrical performance. On the other hand, the conductive carbon material, as a reinforcing phase of the composite structure, can improve the mechanical properties of the entire composite structure, thereby effectively alleviating the stress caused by the volume expansion of nano-silicon during the charging and discharging process, and greatly improving the cycle life of the battery.
[0030] In addition, after being coated with a soft carbon substrate, the size of nano-silicon is increased to the micron level, which can not only effectively increase the tap density and have a higher volumetric capacity at the same mass loading, but the micron-level specific surface area is also beneficial to reduce side reactions, thereby further improving the electrochemical performance of the battery.
[0031] As a preference, at 200 mA g -1 Under the current density of , before and after 50 cycles of treatment, the change rate of metal ion concentration on the surface of the silicon-based negative electrode material includes any point value among 1%, 2%, 4%, 5%, 6%, 8%, 10% or a range value between any two of them, preferably less than or equal to 5%.
[0032] In one embodiment, after 50 cycles of treatment, the metal ion concentration on the surface of the silicon-based negative electrode material is 750ppm-950ppm, including any point value among 750ppm, 800ppm, 850ppm, 900ppm, 950ppm or any range value between two of them.
[0033] In one embodiment, the particle size of the silicon-based negative electrode material is 5 μm-50 μm, including any point value of 5 μm, 7 μm, 15 μm, 25 μm, 40 μm, 50 μm or any range value between two of them.
[0034] In one embodiment, in the silicon-based negative electrode material, the mass fraction of the soft carbon substrate is 20%-90%, preferably 40%-80%; the mass fraction of the nano-silicon is 5%-70%, preferably 10%-50%; the mass fraction of the conductive carbon material is 1%-10%, preferably 1%-5%; the mass fraction of the fast ion conductor is 1%-10%, preferably 1%-5%.
[0035] In one embodiment, the conductive carbon material includes at least one of carbon fiber, carbon nanotube, graphene, silicon carbide or carbon felt.
[0036] In one embodiment, the fast ion conductor includes at least one of silver iodide (AgI), copper iodide (CuI), lithium borate (LiBO2), zirconium oxide (ZrO2), β-alumina (β-Al2O3), and silver sulfide (Ag2S).
[0037] The present invention provides a method for preparing the silicon-based negative electrode material as described above, comprising the following steps:
[0038] S1, mixing a soft carbon precursor, nano-silicon, a conductive carbon material and a fast ion conductor in a solvent to obtain a material, wherein the ionic conductivity of the fast ion conductor is 10 -5 S cm -1 -10 -2S cm -1 , the ion conductance activation energy is 0.2eV-0.4eV;
[0039] S2, performing secondary calcination treatment on the material under protective atmosphere conditions to obtain a silicon-based negative electrode material.
[0040] The preparation method provided by the present invention adopts a soft carbon precursor, nano-silicon, a conductive carbon material and a fast ion conductor with specific ionic conductivity and ionic conductivity activation energy to mix and perform multi-stage calcination, which not only enables the fast ion conductor to form a special negative ion phase near the conductive carbon material, accelerates the ion transmission rate of the silicon-based negative electrode material, significantly improves the electrochemical performance of the material, but also can stably exist in the carbon layer before and after cycling.
[0041] In step S1, based on 100 parts by weight of nano-silicon, preferably, the soft carbon precursor is 160 parts by weight to 1600 parts by weight, the conductive carbon material is 1 part by weight to 50 parts by weight, and the fast ion conductor is 1 part by weight to 50 parts by weight.
[0042] Wherein, the soft carbon precursor includes at least one of asphalt, residual oil, glucose, sucrose, polyvinylidene fluoride, polytetrafluoroethylene or polyimide.
[0043] The conductive carbon material includes at least one of carbon fiber, carbon nanotube, graphene, silicon carbide or carbon felt.
[0044] The fast ion conductor includes at least one of silver iodide (AgI), copper iodide (CuI), lithium borate (LiBO2), zirconium oxide (ZrO2), β-alumina (β-Al2O3), and silver sulfide (Ag2S).
[0045] The solvent includes at least one of tetrahydrofuran, xylene, n-hexane, ether or ethanol.
[0046] In one embodiment, the mixing method includes but is not limited to mechanical ball milling and manual grinding.
[0047] In step S2, the multi-stage calcination treatment preferably includes: the secondary calcination treatment includes: pre-calcining at 450℃-700℃ for 30min-300min, then heating to 700℃-1000℃ at a heating rate of 1℃ / min-10℃ / min and keeping warm for 30min-300min.
[0048] In one embodiment, the protective atmosphere includes but is not limited to at least one of nitrogen, argon, a hydrogen-nitrogen mixture, and a hydrogen-argon mixture.
[0049] The present invention also provides a silicon-based negative electrode material as described above for use in a lithium-ion battery. It is understood that the lithium-ion battery comprises a positive electrode sheet, a negative electrode sheet, a separator, and an electrolyte, wherein the negative electrode sheet uses the silicon-based negative electrode material as an active material.
[0050] It should be noted that the present invention does not limit the preparation method of the negative electrode sheet, and conventional processes can be used. For example, the above-mentioned silicon-based negative electrode material, conductive agent, and binder are mixed in a mass ratio of 80:10:10-94:3:3 to form a slurry, which is coated on the current collector and dried. Among them, the binder includes but is not limited to at least one of sodium carboxymethyl cellulose, sodium alginate, and polyvinylidene fluoride, preferably sodium carboxymethyl cellulose, and the conductive agent includes but is not limited to conductive carbon black, graphite powder, Ketjen black, acetylene black, carbon nanotubes, graphene, etc., preferably conductive carbon black. The solvent used to prepare the slurry is preferably water. The current collector includes copper foil or aluminum foil, the drying temperature is 60℃-120℃, and the drying time is 1h-20h.
[0051] Specifically, the electrolyte includes a lithium salt and a non-aqueous solvent, the lithium salt including but not limited to lithium perchlorate (LiClO4), lithium tetrafluoroborate (LiBF4), lithium hexafluoroarsenate (LiAsF6) and lithium hexafluorophosphate (LiPF6), preferably LiPF6; the non-aqueous solvent includes but not limited to at least one of ethylene carbonate, propylene carbonate, dimethyl carbonate and diethyl carbonate, preferably a mixture of diethyl carbonate and ethylene carbonate.
[0052] The silicon-based negative electrode material, its preparation method and application will be further described below through the following specific examples. However, those skilled in the art will understand that the following examples are only used to illustrate the present invention and should not be regarded as limiting the scope of the present invention. If no specific conditions are specified in the examples, the conventional conditions or the conditions recommended by the manufacturer are followed. The reagents or instruments used without indicating the manufacturer are all conventional products that can be purchased commercially.
[0053] Example 1
[0054] 5g of nano-silicon, 8g of soft carbon precursor, 0.1g of carbon material, 0.1g of fast ion conductor and 20mL of tetrahydrofuran were mechanically mixed and dried. The soft carbon precursor was asphalt, the carbon material was carbon nanotubes, and the fast ion conductor was CuI (with an ionic conductivity of 10 -6 S cm -1 , the ionic conductivity activation energy is 0.38 eV).
[0055] The material obtained above was pre-calcined at 450° C. for 120 min, and then heated to 850° C. at a heating rate of 5° C. / min for secondary calcination for 300 min, with the protective atmosphere being a hydrogen-argon mixed gas.
[0056] Example 2
[0057] 5g of nano-silicon, 8g of soft carbon precursor, 0.2g of carbon material, 0.2g of fast ion conductor and 20mL of tetrahydrofuran were mechanically mixed and dried. The soft carbon precursor was asphalt, the carbon material was carbon nanotubes, and the fast ion conductor was CuI (with an ionic conductivity of 10 -6 S cm -1 , the ionic conductivity activation energy is 0.38 eV).
[0058] The material obtained above was pre-calcined at 450° C. for 120 min, and then heated to 850° C. at a heating rate of 5° C. / min for secondary calcination for 300 min, with the protective atmosphere being a hydrogen-argon mixed gas.
[0059] Example 3
[0060] 5g of nano-silicon, 10g of soft carbon precursor, 0.2g of carbon material, 0.4g of fast ion conductor and 20mL of tetrahydrofuran were mechanically mixed and dried. The soft carbon precursor was asphalt, the carbon material was carbon fiber, and the fast ion conductor was AgI (with an ionic conductivity of 10 -2 S cm -1 , the ionic conductivity activation energy is 0.2 eV).
[0061] The material obtained above was pre-calcined at 450° C. for 180 min, and then heated to 850° C. at a heating rate of 5° C. / min for secondary calcination for 300 min, with a protective atmosphere of a hydrogen-argon mixed gas.
[0062] Example 4
[0063] 5g of nano-silicon, 15g of soft carbon precursor, 0.4g of carbon material, 0.4g of fast ion conductor and 20mL of tetrahydrofuran were mechanically mixed and dried. The soft carbon precursor was asphalt, the carbon material was carbon fiber, and the fast ion conductor was AgI (with an ionic conductivity of 10 -2 S cm -1 , the ionic conductivity activation energy is 0.2 eV).
[0064] The material obtained above was pre-calcined at 450° C. for 180 min, and then heated to 850° C. at a heating rate of 5° C. / min for secondary calcination for 300 min, with a protective atmosphere of a hydrogen-argon mixed gas.
[0065] Example 5
[0066] 5g of nano-silicon, 25g of soft carbon precursor, 0.6g of carbon material, 0.6g of fast ion conductor and 20mL of ethanol were mechanically mixed and dried. The soft carbon precursor was glucose, the carbon material was carbon felt, and the fast ion conductor was β-Al2O3 (with an ionic conductivity of 10 -2 S cm -1 , the ionic conductivity activation energy is 0.25 eV).
[0067] The material obtained above was pre-calcined at 500° C. for 180 min, and then heated to 900° C. at a heating rate of 5° C. / min for secondary calcination for 300 min, with a protective atmosphere of a hydrogen-argon mixed gas.
[0068] Example 6
[0069] 5g of nano-silicon, 50g of soft carbon precursor, 0.8g of carbon material, 1.0g of fast ion conductor and 20mL of ethanol were mechanically mixed and dried. The soft carbon precursor was glucose, the carbon material was silicon carbide, and the fast ion conductor was ZrO2 (with an ionic conductivity of 10 -4 S cm -1 , the ionic conductivity activation energy is 0.4 eV).
[0070] The material obtained above was pre-calcined at 600° C. for 180 min, and then heated to 1000° C. at a heating rate of 5° C. / min for secondary calcination for 300 min, with a protective atmosphere of a hydrogen-argon mixed gas.
[0071] Comparative Example 1
[0072] 5 g of nano-silicon, 8 g of a soft carbon precursor and 20 mL of tetrahydrofuran were mechanically mixed and then dried. The soft carbon precursor was asphalt.
[0073] The material obtained above was pre-calcined at 450° C. for 120 min, and then heated to 850° C. at a heating rate of 5° C. / min for secondary calcination for 300 min, with the protective atmosphere being a hydrogen-argon mixed gas.
[0074] Comparative Example 2
[0075] 5 g of nano-silicon, 15 g of a soft carbon precursor and 20 mL of tetrahydrofuran were mechanically mixed and then dried. The soft carbon precursor was asphalt.
[0076] The material obtained above was pre-calcined at 450° C. for 120 min, and then heated to 850° C. at a heating rate of 5° C. / min for secondary calcination for 300 min, with the protective atmosphere being a hydrogen-argon mixed gas.
[0077] Comparative Example 3
[0078] 5 g of nano-silicon, 25 g of soft carbon precursor and 20 mL of ethanol were mechanically mixed and dried. The soft carbon precursor was glucose.
[0079] The material obtained above was pre-calcined at 500° C. for 180 min, and then heated to 900° C. at a heating rate of 5° C. / min for secondary calcination for 300 min, with a protective atmosphere of a hydrogen-argon mixed gas.
[0080] Comparative Example 4
[0081] 5 g of nano-silicon, 50 g of soft carbon precursor and 20 mL of ethanol were mechanically mixed and dried. The soft carbon precursor was glucose.
[0082] The material obtained above was pre-calcined at 600° C. for 180 min, and then heated to 1000° C. at a heating rate of 5° C. / min for secondary calcination for 300 min, with a protective atmosphere of a hydrogen-argon mixed gas.
[0083] Comparative Example 5
[0084] The difference between Comparative Example 5 and Example 4 is that AgI is replaced by titanium dioxide (with an ionic conductivity of 2.2×10 - 6 S cm -1 , the ionic conductivity activation energy is 0.5 eV).
[0085] Comparative Example 6
[0086] The difference between Comparative Example 6 and Example 4 is that AgI is replaced by aluminum metaphosphate (with an ionic conductivity of 10 -6 S cm -1 , the ionic conductivity activation energy is 0.6 eV).
[0087] Comparative Example 7
[0088] The difference between Comparative Example 7 and Example 4 is that AgI is replaced by Li 10 GeP2S 12 (The ionic conductivity is 5×10 -8 cm -1 , the ionic conductivity activation energy is 0.7 eV).
[0089] The silicon-based negative electrode materials prepared in Examples 1-6 and Comparative Examples 1-7 were characterized and tested for performance. The test results are as follows: Figure 1-4 And as shown in Table 1.
[0090] Performance test: Weigh 450mg silicon-based negative electrode material, 25mg conductive carbon black, 25mg carboxymethyl cellulose, add appropriate amount of deionized water and use planetary ball mill for 2h, apply the milled slurry on the current collector, dry it in vacuum at 80℃ for 12h, and cut it into negative electrode sheets with a diameter of 12mm. Use metallic sodium as the counter electrode and reference electrode, use glass fiber diaphragm as the diaphragm, use LiPF6 with a concentration of 1mol / L as the electrolyte, and use a mixed solution of diethyl carbonate and ethylene carbonate (volume ratio of 1:1) as the solvent. Assemble button cells in a glove box with argon atmosphere. The electrochemical performance of the button cells was tested on the Xinwei battery test system. The charge and discharge voltage range was 0-2V, the current density was 0.2C, and 1C=1000mA / g.
[0091] Test of ion concentration: According to the above-mentioned cycle performance test method, the batteries of each embodiment and comparative example were cycled 50 times, and the batteries were disassembled in a fully charged state. Then, the negative electrode sheet was immersed in an equal volume (100 mL) of deionized water for 10 minutes, and then vacuum filtered. The corresponding metal ion components in the test liquid were detected by inductively coupled plasma emission spectroscopy (ICP), and the metal ion content on the surface of the negative electrode of each embodiment was tested.
[0092] Table 1
[0093]
[0094]
[0095] It can be seen from Table 1 that the silicon-based negative electrode material of the present invention has both electron-ion conductivity and can be used in lithium-ion batteries to improve battery performance and increase cycle life, which is beneficial to ensuring the safety of battery use.
[0096] The technical features of the above-described embodiments may be arbitrarily combined. To make the description concise, not all possible combinations of the technical features in the above-described embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.
[0097] The above-mentioned embodiments only express several implementation methods of the present invention, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the invention patent. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, and these all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.
Claims
1. A silicon-based negative electrode material, characterized in that: The silicon-based negative electrode material comprises a soft carbon substrate and nano-silicon, a conductive carbon material and a fast ion conductor distributed in the soft carbon substrate, wherein the ion conductivity of the fast ion conductor is 10 -5 S cm -1 -10 -2 S cm -1 , the ion conduction activation energy is 0.2eV-0.4eV, and the fast ion conductor forms a negative ion phase on the surface of the conductive carbon material; At 200mA·g -1 At a current density of , before and after 50 cycles of treatment, the change rate of metal ion concentration on the surface of the silicon-based negative electrode material is less than or equal to 10%.
2. The silicon-based negative electrode material according to claim 1, characterized in that: After 50 cycles of treatment, the metal ion concentration on the surface of the silicon-based negative electrode material is 750ppm-950ppm.
3. The silicon-based negative electrode material according to claim 1, characterized in that: The particle size of the silicon-based negative electrode material is 5 μm-50 μm.
4. The silicon-based negative electrode material according to claim 1, characterized in that: In the silicon-based negative electrode material, the mass fraction of the soft carbon substrate is 20%-90%, the mass fraction of the nano-silicon is 5%-70%, the mass fraction of the conductive carbon material is 1%-10%, and the mass fraction of the fast ion conductor is 1%-10%.
5. The silicon-based negative electrode material according to claim 1, characterized in that: The conductive carbon material includes at least one of carbon fiber, carbon nanotube, graphene, silicon carbide or carbon felt.
6. The silicon-based negative electrode material according to claim 1, characterized in that: The fast ion conductor includes at least one of silver iodide, copper iodide, lithium borate, zirconium oxide, β-aluminum oxide or silver sulfide.
7. A method for preparing a silicon-based negative electrode material according to any one of claims 1 to 6, characterized in that: The steps include: A soft carbon precursor, nano-silicon, a conductive carbon material and a fast ion conductor are mixed in a solvent to obtain a material, wherein the ionic conductivity of the fast ion conductor is 10 -5 S cm -1 -10 -2 S cm -1 , the ion conductance activation energy is 0.2eV-0.4eV; The material is subjected to secondary calcination treatment under protective atmosphere conditions to obtain a silicon-based negative electrode material.
8. The method for preparing a silicon-based negative electrode material according to claim 7, characterized in that: Based on 100 parts by weight of nano-silicon, the soft carbon precursor is 160 parts by weight to 1600 parts by weight, the conductive carbon material is 10 parts by weight to 100 parts by weight, and the fast ion conductor is 10 parts by weight to 100 parts by weight; And / or, the soft carbon precursor includes at least one of asphalt, residual oil, glucose, sucrose, polyvinylidene fluoride, polytetrafluoroethylene or polyimide; And / or, the solvent includes at least one of tetrahydrofuran, xylene, n-hexane, ether or ethanol.
9. The method for preparing a silicon-based negative electrode material according to claim 7, characterized in that: The secondary calcination treatment includes: pre-calcining at 450-700°C for 30-300 minutes, then heating to 700-1000°C at a heating rate of 1-10°C / min and keeping the temperature for 30-300 minutes.
10. A silicon-based negative electrode material as claimed in any one of claims 1 to 6 for use in a lithium-ion battery.